Induced current density evaluation in organs of a human, located in the overhead power lines passage zone - Sergey Yu. Perov; Valentina S. Orlova; Vladimir V. Zhurov (RUDN Journal of Ecology and Life Safety)
Based on the results of field measurements, during which exceedances of maximum permissible levels of electric field strength (up to 11.5 kV/m) were recorded, mathematical models of the ecological situation of electric and magnetic fields of industrial frequency near the passage of ultra-high voltage power lines have been developed. The combined effect of ultra-low-frequency electric and magnetic fields on the human body in the context of the density of induced currents in organs has been analyzed. Special attention is paid to the analysis of organ systems that are most exposed to the biological effects of the factor. Modeling with the use of human phantom revealed the density of induced currents in the nervous, visual, endocrine systems exceeding the norms (up to 161.5247 mA/m²). The analysis of gradation of the factor influence depending on the location of a person directly from the source of electric and magnetic fields of industrial frequency has been carried out and it has been confirmed that the greatest influence occurs under the projection of the middle phase under the maximum sag and decreases at removal of a person from the sag to the support itself or to the boundaries of the sanitary protection zone.